2016
DOI: 10.5152/tjar.2016.76992
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic Management of Children with Rubinstein-Taybi Syndrome

Abstract: Rubinstein-Taybi Sendromu (RTS); geniş başparmak, büyük ve geniş ayaklar, boy kısalığı ve kraniyofasiyal anormallikler gibi fiziksel değişiklikler ve mental retardasyon ile kendini gösteren, nadir, otozomal dominant bir sendromdur. Anestezi açısından, zor havayolu, aspirasyon pnömonisi ve kardiyovasküler işlev bozukluğu özellikle dikkat edilmesi gereken durumlardır. Mikrognati, retrognati, geniş burun köprüsü, anormal derecede büyük ya da "gaga şeklinde" burun, hipoplastik maksilla ve küçük ağız tipik dismorfi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…When selecting anesthesia, meticulous care is recommended to reduce these risks. 27 , 28 For example, Stirt and Karahan et al suggested that anesthetic agents such as atropine, succinylcholine, and neostigmine be avoided because they increase the risk of arrhythmia. 27 , 28 Preoperative examination excluded heart disease in our patient, and no heart failure or arrhythmia occurred during surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When selecting anesthesia, meticulous care is recommended to reduce these risks. 27 , 28 For example, Stirt and Karahan et al suggested that anesthetic agents such as atropine, succinylcholine, and neostigmine be avoided because they increase the risk of arrhythmia. 27 , 28 Preoperative examination excluded heart disease in our patient, and no heart failure or arrhythmia occurred during surgery.…”
Section: Discussionmentioning
confidence: 99%
“… 27 , 28 For example, Stirt and Karahan et al suggested that anesthetic agents such as atropine, succinylcholine, and neostigmine be avoided because they increase the risk of arrhythmia. 27 , 28 Preoperative examination excluded heart disease in our patient, and no heart failure or arrhythmia occurred during surgery. Intellectual disability in our patient was mild (an estimated delay of 2–3 years) and allowed for normal communication, thereby limiting the restrictions on peri- and postoperative practices.…”
Section: Discussionmentioning
confidence: 99%
“…Micrognathia, retrognathia, broad nasal bridge, beak-shaped nose, hypoplastic maxilla and small mouth usually lead to potential difficulties with airway management for anaesthesia and surgery 4. The presence of cervical hyperkyphosis (incidence of 62%) and scoliosis (incidence of 36%) may also make it difficult to align the axes of the oral cavity, pharynx and trachea, in order provide an optimal position during tracheal intubation 4. In our case, intubation was successfully performed with the aid of a video laryngoscope.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery to correct a delta phalanx deformity (Wood and Rubinstein 1987) 9. Caution with general anesthesia in children (Stirt 1981;Karahan et al 2016) 1. Challenging to intubate due to airway anomalies.…”
Section: Many Clinical Geneticists and Geneticmentioning
confidence: 99%